Dinasti Politik pada Pemerintahan di Tingkat Lokal - Adelia Fitri (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2019)
This paper will explore the phenomenon of local politicians who perpetuate power through political dynasties at the local government level. This is important to discuss because Indonesia as a democratic country in an era of transparency and accountability needs visionary leaders who properly represent the people in accordance with their capacities and capabilities. The focus of this study examines the electoral system that occurs at the local level through politicians who build political dynasties in Riau Islands Province. Riau Islands Province was made a study area because there were still phenomena of families becoming politicians in the 2019 general election. To obtain comprehensive data, the authors used research data collection through library research. The results of the study found that political dynasties can occur due to several factors, among others, in the context of a plural or plural society such as Indonesia, individual political behavior will be strongly influenced by the production of social, economic, psychological, historical, political and cultural factors. Second, the absence of periodic restrictions makes candidates who have charismatic and popularity in the community continue to run themselves as a great opportunity for families to participate in electoral politics at the local level.